2018
DOI: 10.1021/acscatal.8b03391
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Choice for Highly Enantioselective [3 + 3]-Cycloaddition of Enoldiazocarbonyl Compounds

Abstract: Chiral copper(I) catalysts are preferred over chiral dirhodium(II) catalysts for [3 + 3]-cycloaddition reactions of enoldiazocarbonyl compounds with nitrones and acyliminopyridinium ylides, forming chiral oxazines and pyrazines in very high yield and enantioselectivity. Yields and stereoselectivities from reactions of enoldiazoketones are virtually the same as those from the corresponding esters and amides, but products from enoldiazoketones are precursors to chiral 1,3-dicarbonyl derivatives that provide addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The copper(I)-catalyzed [3+3]-cycloaddition of nitrones 10 using silyl-protected enoldiazoacetates, 39 -acetamides, 39,40 -ketones 39 and -sulfones 41 (9) (Scheme 5) illustrates the exceptional selectivity that can be achieved in these transformations as well as their inherent complexity. Because of their inherent stability, nitrones are popular for catalytic dipolar cycloaddition transformations.…”
Section: Asymmetric [3+3]-cycloaddition 41 Nitronesmentioning
confidence: 99%
See 4 more Smart Citations
“…The copper(I)-catalyzed [3+3]-cycloaddition of nitrones 10 using silyl-protected enoldiazoacetates, 39 -acetamides, 39,40 -ketones 39 and -sulfones 41 (9) (Scheme 5) illustrates the exceptional selectivity that can be achieved in these transformations as well as their inherent complexity. Because of their inherent stability, nitrones are popular for catalytic dipolar cycloaddition transformations.…”
Section: Asymmetric [3+3]-cycloaddition 41 Nitronesmentioning
confidence: 99%
“…4b, [10][11][12][13]42 In previous investigations of nitrone cycloaddition reactions with enoldiazoacetates, copper(I) catalysis was not as effective or selective as catalysis by chiral rhodium(II) carboxylates 43 or silver(I)/t-BuBOX. 44 However, reinvestigation of this process revealed that enoldiazocarbonyl compounds and enoldiazosulfones offered consistently higher yields and enantioselectivities under copper(I) catalysis [39][40][41] than did the corresponding enoldiazoacetates under rhodium(II) catalysis. 43 The key factor in this discovery was the modification of the chiral box ligands on copper, and the greater electrophilic reactivity of these copper catalysts over chiral dirhodium carboxylate catalysts.…”
Section: Asymmetric [3+3]-cycloaddition 41 Nitronesmentioning
confidence: 99%
See 3 more Smart Citations